Omzet Meroket Berkat Kuliner pedas: Efek Citra Rasa Pedas pada Peningkatan Penjualan - Septiani, Dea; Fachri, Rifky Muhammad (International Journal Administration, Business & Organization, 2024)
This research explores how spicy flavors impact sales in the culinary industry. This research uses a descriptive quantitative approach to examine consumer preferences for spicy food in Bandung City. Data was collected through questionnaires given to 180 people to rate their preference for spicy food using a Likert scale. The results of this study show that the level of spiciness significantly influences the increase in sales in the culinary industry. Consumers in the current generation, especially Gen Z, tend to prefer spicy food, impacting their decision to purchase products and their loyalty. Psychological and cultural factors also affect heat preferences, suggesting that varying heat intensity may be a viable strategy for capturing consumer attention. The findings suggest that companies with a spicy flavor image can improve their competitiveness and increase sales by developing products and marketing strategies that match current consumer preferences.